The roles of SMEs in implementing CSR in supply chains: a systematic literature review. Issue 3 (3rd May 2020) - Stekelorum, Rébecca
ABSTRACT: In recent years, corporate social responsibility (CSR) has benefited from an increasing interest in supply chains. The creation of a sustainable supply chain usually depends of small- and medium-sized enterprises (SMEs)' ability to work with CSR issues. However, scholars have paid less attention to CSR practices in SME supply chains. Therefore, the purpose of this paper is to provide a systematic literature review of the implementation of CSR practices in the supply chains of SMEs. Using a set of 63 papers, this study develops a conceptual framework that encompasses four different roles of SMEs in implementing CSR in the supply chain (adopters, brokers, generators, and transmitters). This study also identifies four SME characteristics and five contingency factors that are related to the different roles of SMEs. This paper draws on the perspective of SMEs, which has been less studied by academia but has a substantial impact on the overall economy.